Methodology for Assessing the Quality of Educational Services in Higher Education - V., VINOGRADOVA MARINA; OLGA S., KULYAMINA; LIDIA A., VASILEVA; EVGENIYA M., BRONNIKOVA; VIKTORIYA A., VISHNYAKOVA (The journal of contemporary issues in business and government, 2021)
Annotation: The article examines the criteria and indicators for assessing the quality of educational services. The coverage of the topic of this article passes through the prism of factors related to the assessment of educational services quality, which allowed the authors to identify current methodological problems, as well as to emphasize the importance of using an integrated approach in studying the issues of providing educational services. The authors identify criteria and indicators for assessing of educational services. The authors developed the composite coefficient of educational services quality. The practical implementation of the proposals prepared by the authors determines the prerequisites for the development of a methodology for assessing educational services quality, which will allow for an objective assessment and, as a result, take the necessary measures to improve the quality of educational services on the part of the educational organization.